The difference of location for the workforce in the Education sector in the center of Kalar district - Chiman Omer Abdulrahman; Sarkawt Hamakhursheed Ahmed; San Salar Sami ALASAADI; Narmin Abdulla Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
In today's world of work one of the different sectors has been able to play a major role in the needs of society and the world. It is one of the sectors that directly affects the individual's life and has become a factor in the world's control over the world، the economic sector is a major necessity of society and reflects the progress that society has achieved. The importance of conducting this study is that it discusses an important and influential aspect in the area of population geography: the labor force at the level of the Ministry of Education in The city of Kalar. The aim of this research is to identify the research area and to know the level of labor force in the Ministry of Education in the research area. In the center of Kalar city، the total number of employees and teachers is only 8، and 3723 employees and permanent teachers are in the Kalar city area and the highest workforce according to the certificates.